2020
DOI: 10.3390/jcm9082679
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Kidney Injury Following Major Abdominal Surgery: A Contemporary Review

Abstract: Acute kidney injury (AKI) is a frequent occurrence following major abdominal surgery and is independently associated with both in-hospital and long-term mortality, as well as with a higher risk of progressing to chronic kidney disease (CKD) and cardiovascular events. Postoperative AKI can account for up to 40% of in-hospital AKI cases. Given the differences in patient characteristics and the pathophysiology of postoperative AKI, it is inappropriate to assume that the management after noncardiac and nonvascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 139 publications
0
13
0
1
Order By: Relevance
“…Cisplatin tubulopathy features electrolytic disturbances (mainly hypomagnesemia and hypokalemia) and acute kidney injury (AKI). AKI is a common syndrome characterized by an abrupt decline in glomerular filtration rate (GFR), severe azotemia, and, often, oliguria or anuria [ 7 , 14 ]. Additionally, endothelial dysfunction that increases renal vascular resistance and impairs autoregulation also contributes to cisplatin-induced AKI [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cisplatin tubulopathy features electrolytic disturbances (mainly hypomagnesemia and hypokalemia) and acute kidney injury (AKI). AKI is a common syndrome characterized by an abrupt decline in glomerular filtration rate (GFR), severe azotemia, and, often, oliguria or anuria [ 7 , 14 ]. Additionally, endothelial dysfunction that increases renal vascular resistance and impairs autoregulation also contributes to cisplatin-induced AKI [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, endothelial dysfunction that increases renal vascular resistance and impairs autoregulation also contributes to cisplatin-induced AKI [ 9 ]. Ordinarily, AKI is a reversible condition, which nonetheless has a relevant impact on patient outcomes, including elevated in-hospital mortality (over 50% of cases among the critically ill), prolonged hospitalization, additional health care costs, and, in the middle- and long-term scenarios, increased risk of developing chronic kidney disease and of general and cardiovascular morbimortality [ 7 , 14 ]. At the subcellular and molecular levels, cisplatin tubular cytotoxicity is driven by mitochondrial injury, which curtails respiration, produces oxidative stress, and induces apoptotic and necrotic cell death and a deleterious inflammatory response [ 13 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that the cut-off value varies based on the disease's case or cause. 22,23 As it was known that the NGAL levels describe the injury to the kidney, its value is also influenced by several factors including inflammatory, infection, intoxication, ischemia, and neoplasia. 24 The majority of existing studies state that the cut-off value of NGAL was in cases of intensive care sepsis and very rarely in postoperative cases.…”
Section: Discussionmentioning
confidence: 99%
“…Through a process of risk stratification on the basis of previous history, along with planned surgical procedure, this information could then be used to inform a multidisciplinary team regarding preoptimization, surgical technique used, and postoperative destination. Pharmacologic management of AKI has been extensively investigated but, at present, there is no strong evidence to recommend a particular drug therapy (28,66). This may be due to inadequate risk stratification of patients and, as mentioned, biomarkers or models may aid future research here.…”
Section: Management Of Postoperative Akimentioning
confidence: 99%